If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12C + C = 7C + 18 Combine like terms: 12C + C = 13C 13C = 7C + 18 Reorder the terms: 13C = 18 + 7C Solving 13C = 18 + 7C Solving for variable 'C'. Move all terms containing C to the left, all other terms to the right. Add '-7C' to each side of the equation. 13C + -7C = 18 + 7C + -7C Combine like terms: 13C + -7C = 6C 6C = 18 + 7C + -7C Combine like terms: 7C + -7C = 0 6C = 18 + 0 6C = 18 Divide each side by '6'. C = 3 Simplifying C = 3
| 3g-49=47 | | 5m+7n=35 | | x^4-11x^2+28=x | | 6-y=2y | | 6n+10=3 | | 9(1+9k)= | | 0.14=0.0001 | | u^2+250=0 | | M^2+3M= | | -15/-5=3 | | 0.13=0.001 | | x-7.5=-2x | | -6x=4y+1 | | 14+3n=8n-3+(n-4) | | 8(4-M)=8+4M | | 2l=5l-60 | | 88.1-2.3=72.46 | | 0.12=0.01 | | 200000+(60)=300000+(25) | | 3=3+5k-5 | | 6x+5=2x-3 | | 12+(x+9)=7 | | 2l=60-5l | | -42p-4p=-12 | | -15.3=7.5+55.2 | | 35(100000)= | | 0=-4.9t^2+19.6t+58.8 | | 2(l)=60-5(l) | | h=-4.9t^2+19.6t+58.8 | | -2x+7y=-9 | | 10x+5=26 | | =3x+x+x+5+2x+3+x+5 |